2012
DOI: 10.1590/s0004-27492012000100006
|View full text |Cite
|
Sign up to set email alerts
|

Single intravitreal bevacizumab injection effects on contrast sensitivity in macular edema from branch retinal vein occlusion

Abstract: Purpose: To evaluate the effect of a single intravitreal bevacizumab injection on visual acuity, contrast sensitivity and optical coherence tomographymea su red cen tral macular thickness in eyes with macular edema from branch re tinal vein occlusion. Methods: Seventeen eyes of 17 patients with macular edema from unilateral branch retinal vein occlusion were treated with a single bevacizumab injection. Patients were submitted to a complete evaluation including best corrected visual acuity, contrast sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…Recently, Preti et al evaluated the change in CS function after intravitreal injection of bevacizumab for the treatment of ME secondary to BRVO [13]. They found that eyes with ME showed an improvement in VA 1 month after bevacizumab injection, but VA again worsened at 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Preti et al evaluated the change in CS function after intravitreal injection of bevacizumab for the treatment of ME secondary to BRVO [13]. They found that eyes with ME showed an improvement in VA 1 month after bevacizumab injection, but VA again worsened at 3 months.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 Although there are limited baseline data on the CS of patients with RVO as compared to controls, CS measurements have demonstrated value in assessing ischemic retinal diseases and have characterized visual changes in RVO post-treatment. 6 , 7 In order to better characterize vision loss in RVO, a more robust understanding of CS changes in RVO is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Measures of visual function other than visual acuity after anti-VEGF treatment of BRVO have been reported in a few papers [6][7][8][9]. Suner et al [6] reported improvements in reading speed as estimated by the reading speed test developed by the Macular Photocoagulation Study Group.…”
Section: Introductionmentioning
confidence: 99%
“…Varma et al [7] measured the NEI VFQ-25, another indicator of visual function, during BRVO treatment via intravitreal injection of ranibizumab. Preti et al [8] reported that a single intravitreal bevacizumab injection improved contrast sensitivity (CS) in macular edema from BRVO. Pece et al [9] reported that CS, MNREAD time, and reading fluency improved significantly in eyes treated with ranibizumab.…”
Section: Introductionmentioning
confidence: 99%